Assessing The Adequacy of the Kirkpatrick Model in Evaluating The Performance of Public Sector Apparatus Training: A Post-Learning Evaluative Study of Distance Learning Training at The Tax Education and Training Center - Dito Mahar Putro; Iwan Kurniawan Subagja; Azis Hakim (Dinasti Publisher, 2026)
This study aims to assess the adequacy of the Kirkpatrick Model in evaluating the performance of distance learning (PJJ)-based public sector apparatus training through a post-learning evaluation approach. The research focuses on four distance learning (PJJ) programs organized by the Tax Education and Training Center (Pusdiklat Pajak). This study uses a model-oriented evaluation approach with an evaluative case study design. The data used are sourced from Level 3 and Level 4 Post-Learning Evaluation (Epaspem) reports, which are analyzed using mixed methods with a limited explanatory approach. Quantitative analysis is used to assess the empirical performance of the Kirkpatrick Model at Level 3 (behavior) and Level 4 (outcomes), while qualitative analysis is conducted to examine the model's limitations in representing evaluation results in the context of distance learning and the public sector. The results show that the Kirkpatrick Model is able to identify changes in work behavior and provide an overview of the short-term work outcomes of alumni in the four distance learning programs. However, this model still has limitations, especially in explaining impact attribution and in representing organizational performance more comprehensively.